Formulasi Kebijakan Corporate Social Responsibility (CSR) Dalam Mendukung Pembangunan Berkelanjutan - Sabaruddin Panrecalle (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
CSR conceptually is in line with the sustainable development agenda. Local governments need to map the potential of CSR as an instrument to support development in their region. Using this type of exploratory research, this study aims to describe phenomena in the formulation of CSR policies in Balikpapan City. Public policy theory is the basis for examining it, which is combined with discourse on the triple bottom line. There are three pillars for this, namely profit, planet, and people. The findings in this study reveal that the CSR policy formulation process has gone through the following stages: The problem Formulation Stage, the Policy Agenda Stage, the Policy Alternative Selection Stage to Solve Problems, and the Policy Determination Stage. Several actors were involved during the formulation, Members of the legislature (DPRD), Balikpapan City Government, NGOs, Universities, and companies in Balikpapan City. Based on these dynamics, the system model colors the formulation of CSR policies in the research area.